Penerapan Metode Pembelajaran Mind Mapping untuk Meningkatkan Hasil Belajar Peserta Didik Kelas VIII SMP Negeri 2 Sungguminasa (Studi pada Materi Pokok Sistem Pencernaan Manusia) - Nur Kholiffa Andriyani Massi; Sitti Saenab; Salma Samputri (Universitas Negeri Makassar, 2025)
This study aims to find out: 1) the learning outcomes of grade VIII students of SMP Negeri 2 Sungguminasa before and after the application of the Mind Mapping learning method. 2) improving the learning outcomes of grade VIII students at SMP Negeri 2 Sungguminasa through the application of the Mind Mapping learning method. 3) the application of the Mind Mapping learning method can significantly improve learning outcomes in grade VIII students of SMP Negeri 2 Sungguminasa. This type of research is Pre-Experiment Design research and One Group Pretest-Posttest Design research design. The population of this study is all students in grade VIII of SMP Negeri 2 Sungguminasa for the 2024/2025 school year, the sample was selected by purposive sampling of 29 students. The research instrument is in the form of a learning outcome test. The data were analyzed with descriptive and inferential statistics. The results of the analysis concluded: 1) the category of learning outcomes of students in grade VIII of SMP Negeri 2 Sungguminasa before the implementation of the Mind Mapping learning method obtained a learning outcome score of 10.89 which was in the low category, while after the implementation of the Mind Mapping learning method, a learning outcome score of 16 was obtained which was in the high category. 2) the improvement of the learning outcomes of grade VIII students of SMP Negeri 2 Sungguminasa through the application of the Mind Mapping learning method obtained an average N-Gain on learning outcomes of 0.56 which is in the medium category, 3) the application of the Mind Mapping learning method can significantly improve learning outcomes in grade VIII students of SMP Negeri 2 Sungguminasa.